A Practical Methodology for Photovoltaic Development at a Thai Educational University - Hiranvarodom, Somchai (Frontiers in Engineering Innovation Research, 2006)
This paper presents the methodology of the development for photovoltaic (PY) systems, all of them are stand alone types that have been installed in Rajamangala University of Technology Thanyaburi (RMUTT) which is located at Klong 6, Thanyaburi district of Pathumthani province in Thailand. The main objective for installation these energy systems is to promote some solar energy projects in terms of PY systems based on the university’s energy policy. The PY projects were partially supported by the government’ s budget, for example the pumping system. street lighting, solar home system. board of the Faculty map and so on. The system s have providing an installed of capacity around 2,170 W[subscript p] The resultant information will include the system performance over a two year monitoring period and together with some operational experiences in terms of reliability and maintenance, acceptability and user satisfaction. However, the life cycle cost of each system is comparable and the key issues discussed in the paper are the problems encountered under installation.